Forgotten God : reversing our tragic neglect of the Holy Spirit - Chan, Francis; Yankoski, Danae (Colorado Springs, CO : David C. Cook, 2009)
It doesn't make sense that Almighty God would have children characterized by fear and insecurity. Could it be that we've forgotten the One who distinguishes us from every other religion and cult in the world? Chan returns us to the Holy Spirit as the Bible describes Him.
I've got Jesus. Why do I need the Spirit? -- What are you afraid of? -- Theology of the Holy Spirit 101 -- Why do you want Him? -- A real relationship -- Forget about His will for your life! -- Supernatural church.
Includes bibliographical references (p. 167).
Keywords: Holy Spirit; Spiritual life -- Christianity